2002
DOI: 10.1002/cncr.10301
|View full text |Cite
|
Sign up to set email alerts
|

Idiotypic-anti-idiotypic complexes and their in vivo metabolism

Abstract: BACKGROUND Different strategies can be used to improve the tumor:non‐tumor ratio of radiolabeled antibodies in immunotargeting. One approach is to use secondary antibodies to clear out redundant, circulating primary antibodies. In the current study, the in vitro complex formation and in vivo clearing capabilities and metabolism of the monoclonal antibody TS1 and its monoclonal anti‐idiotype, αTS1, were studied. METHODS Complex formation studies were performed using polyacrylamide gel electrophoresis (PAGE), ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 23 publications
4
16
0
2
Order By: Relevance
“…As formation of these complexes in vivo could be impacted by the antibody dose and affinity (more stable complexes can form with higher affinity antibodies), it is possible that increases in antibody-antigen binding in circulation may translate into lower serum and tissue exposure when a more rapid clearance of the complex is anticipated. This hypothesis is supported by previous experimental data demonstrating formation of large immune complexes in mice following simultaneous administration of a therapeutic antibody with its anti-idiotypic counterpart (43). As suggested by theoretical simulations shown in Fig.…”
Section: Role Of Fcrn In Antibody Pharmacokinetics and Distributionsupporting
confidence: 83%
“…As formation of these complexes in vivo could be impacted by the antibody dose and affinity (more stable complexes can form with higher affinity antibodies), it is possible that increases in antibody-antigen binding in circulation may translate into lower serum and tissue exposure when a more rapid clearance of the complex is anticipated. This hypothesis is supported by previous experimental data demonstrating formation of large immune complexes in mice following simultaneous administration of a therapeutic antibody with its anti-idiotypic counterpart (43). As suggested by theoretical simulations shown in Fig.…”
Section: Role Of Fcrn In Antibody Pharmacokinetics and Distributionsupporting
confidence: 83%
“…There are two possible scenarios in which ADA can alter the PK of biotherapeutic drugs: 1. ADA reducing the drug exposure (11)(12)(13)(14), and 2. ADA can increase the drug exposure (15,16).…”
Section: Impact Of Ada On Pk Evaluationmentioning
confidence: 99%
“…However, evidence of both mechanisms exists. For example, ADA-mediated assay interferences have been identified through the use of orthogonal PK assay formats that are applied to identical ADA-positive study samples (20,21 125 -labelled anti-idiotypic antibody increased as the molar stoichiometry of the anti-idiotypic antibody and target antibody increased, presumably due to the enhanced uptake and destruction by macrophages when antibodies are cross-linked in higher-order complexes (14).…”
Section: Impact Of Ada On Pk Evaluationmentioning
confidence: 99%
“…Second, the ADA could alter the PK of the compound. It has been shown that the formation of immune complexes between ADA and the administered mAb can change the biodistribution of mAb and lead to faster clearance (41,42). Lastly, circulating ADA could effectively compete with the binding of mAbs and interfere with analytical assays.…”
Section: Understanding Immunogenicity and Antidrug Antibodiesmentioning
confidence: 99%